Heterogeneous nuclear ribonucleoprotein K is associated with poor prognosis and regulates proliferation and apoptosis in bladder cancer - Chen, Xu (J Cell Mol Med, 2016)
Heterogeneous nuclear ribonucleoprotein K (hnRNPK) is an essential RNA‐ and DNA‐binding protein that regulates diverse biological events, especially DNA transcription. hnRNPK overexpression is related to tumorigenesis in several cancers. However, both the expression patterns and biological mechanisms of hnRNPK in bladder cancer are unclear. We investigated hnRNPK expression by immunohistochemistry in 188 patients with bladder cancer, and found that hnRNPK expression levels were significantly increased in bladder cancer tissues and that high‐hnRNPK expression was closely correlated with poor prognosis. Loss‐ and gain‐of‐function assays demonstrated that hnRNPK promoted proliferation, anti‐apoptosis, and chemoresistance in bladder cancer cells in vitro, and hnRNPK knockdown suppressed tumorigenicity in vivo. Mechanistically, hnRNPK regulated various functions in bladder cancer by directly mediating cyclin D1, G0/G1 switch 2 (G0S2), XIAP‐associated factor 1, and ERCC excision repair 4, endonuclease catalytic subunit (ERCC4) transcription. In conclusion, we discovered that hnRNPK plays an important role in bladder cancer, suggesting that it is a potential prognostic marker and a promising target for treating bladder cancer.